NEOLITHIC POTTERY PRODUCTION IN SOUTHEAST THESSALY THROUGH THE APPLICATION OF PETROGRAPHY AND MINERALOGY - Pentedeka, Areti; Koutsovitis, Petros; Magganas, Andreas; Rassios, Annie (Bulletin of the Geological Society of Greece, 2019)
The present paper focuses on the raw materials used for the local manufacture of pottery at two Neolithic settlements (Magoula Visviki, Magoula Agrokipiou) in the Velestino region, SE Thessaly, an area characterized by a distinctive ophiolithic sequence and its sedimentary weathering products. The mineralogical composition and rock fragment constituents of pottery fabrics are compared with that of rock and sediment samples from the adjacent area, thus locating the ancient raw material sources that were exploited.